Deep-sea polychaetes (Annelida) from the Malta Escarpment (western Ionian Sea). Issue 1 (1st January 2017) - Langeneck, J.; Busoni, G.; Aliani, S.; Castelli, A.
Abstract: The polychaete assemblages from an escarpment area in the western Ionian Sea are characterised in terms of species richness, evenness and trophic composition. Moreover, the first occurrence of the genus Barantolla in the Mediterranean Sea, and of Lumbrinerides carpinei and Exogone ( Parexogone ) campoyi in Italian waters, is reported. Aricidea trilobata Laubier and Ramos, 1974 is redescribed on the basis of new material with the new name Aricidea ( Acmira ) jeaneteae, together with a brief description of two deep-water species belonging to the genus Levinsenia .